One-pot Synthesis and Antitumor Activity of Unsymmetrical Terphenyls - Punganuru, S. R.; Samala, R.; Srivenugopal, K. S. (Drug Research, 2017)
In this paper a simple and efficient method for the unsymmetrical terphenyls via sequential one-pot Suzuki coupling reactions using Pd(OAc)2 without isolation of the intermediate is described. The prepared terphenyls were found to possess potent anticancer properties against a panel of cancer cells which includes A549, HeLa, MCF7, DU145, HT29 and BxPC-3. Structural similarity with combretastatin A4, these terphenyls disrupted the tubulin polymerization in vitro and destabilized the microtubules in cells. Flow cytometry studies indicated growth arrest of cells in the G2/M phase of the cell cycle corresponding to antimitotic action. Furthermore, compound 4c showed potent anti-mitotic activity even in zebrafish model and could likely be a potential therapeutic compound as it is active both in in vitro and in vivo.
Keywords: terphenyls; combretastatin A4; antimitotic agents; tubulin polymerization inhibition